2021
DOI: 10.1111/cts.13109
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of large volume subcutaneous injection tissue effects, pain, and acceptability in healthy adults

Abstract: were employees of the study sponsor and funding entity, BD (Becton, Dickinson and Company), when the study was performed and may also be stockholders. Funding:Study funding was provided by BD (Becton, Dickinson and Company).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Woodley and colleagues investigated the tolerability of s.c. infusions of 5-10 mL (to the abdomen), or 5 mL (to the thigh) at an infusion flow of 1.2 mL/minute, with a range of solution viscosities to 32 healthy participants. 17 Although this study had some differences in design compared with previous studies that complicate direct comparisons (such as needle gauge, viscosity, and VAS timepoints), the study also reported good tolerability and acceptability of the infusions that were evaluated. When comparing similar infusion conditions from Woodley and colleagues (10 mL infusion to the abdomen at 1.2 mL/minute) to the present studies (cohort C of GP29523, 12 mL test placebo or crenezumab 1,800 mg (12 mL) at 1 mL/minute to the abdomen), Woodley and colleagues report higher median VAS scores during the infusion of ~ 30 mm, compared to 16 mm and 10 mm for test placebo and crenezumab infusions, respectively, in GP29523.…”
Section: Discussionmentioning
confidence: 85%
“…Woodley and colleagues investigated the tolerability of s.c. infusions of 5-10 mL (to the abdomen), or 5 mL (to the thigh) at an infusion flow of 1.2 mL/minute, with a range of solution viscosities to 32 healthy participants. 17 Although this study had some differences in design compared with previous studies that complicate direct comparisons (such as needle gauge, viscosity, and VAS timepoints), the study also reported good tolerability and acceptability of the infusions that were evaluated. When comparing similar infusion conditions from Woodley and colleagues (10 mL infusion to the abdomen at 1.2 mL/minute) to the present studies (cohort C of GP29523, 12 mL test placebo or crenezumab 1,800 mg (12 mL) at 1 mL/minute to the abdomen), Woodley and colleagues report higher median VAS scores during the infusion of ~ 30 mm, compared to 16 mm and 10 mm for test placebo and crenezumab infusions, respectively, in GP29523.…”
Section: Discussionmentioning
confidence: 85%
“…5). While somewhat viscous, the F1S preparation was only mildly hyperosmotic (386 ± 30 mOsm), suggesting that viscous formulations may offer an advantage over hyperosmotic formulations in improving AAV stability at temperatures greater than 4 °C as long as they can be administered with minimal resistance from the injection device and are well tolerated by the patient 48,49 . This specific polymer was selected for use in the previous formulation developed for recombinant adenovirus for its superior filmforming and mucoadhesive properties to improve the potency of vaccines given by oral and nasal routes, for which the platform was specifically designed [24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“… 12 In a recent early clinical feasibility study, SC injections of volumes up to 10 mL (8.2 minutes) in the abdomen and 5 mL (4.1 minutes) in the thigh with viscosities up to 20 cP with a constant rate (20 µl/s) syringe pump system were found to be feasible and tolerable in 32 healthy volunteers. 83 In two recent Phase 1 studies with healthy volunteers, SC administration of crenezumab at volumes ranging from 4 mL (600 mg) to 40 mL (7200 mg) were well tolerated with or without co-formulation with a permeation enhancer (hyaluronidase), and volume, dose, concentration, flow rate (≤4 mL/min), or the presence or absence of hyaluronidase did not appear to affect pain or the type or incidence of TEAEs. 96 Similarly, acceptable tolerability and safety were demonstrated in a study with healthy volunteers using a viscous placebo buffer characteristic of a high-concentration mAb formulation at volumes of 3.5 mL in 3 injections over 1, 4, or 10 minutes in different abdominal quadrants.…”
Section: Development Benefits Of Low-concentration High-volume Formul...mentioning
confidence: 95%
“… 82 In a recent clinical feasibility study with 32 healthy volunteers, no clinically (≥10 mm on a visual analog scale) or statistically significant difference in injection pain was found between 5 mL, 4.1-minute and 10 mL, 8.2-minute injections at a constant rate of 20 µl/s. 83 Higher flow rate and injection speed may be more important considerations for traditional, hand-administered SC devices such as autoinjectors or stationary infusion pumps than for OBDSs, which do not require the patient to hold the device while the drug is delivered and allow for light-to-moderate activities during treatment administration.…”
Section: Subcutaneous Delivery Product Development Considerationsmentioning
confidence: 99%